PENDAMPINGAN PREVENTIF BULLYING MELALUI P5 DI SEKOLAH MENENGAN PERTAMA MANARUL QUR’AN - Mi'ah, Mazrikhatul; Azizah, Nur; Hidayati, Nurul (Universitas Al-Amien Prenduan, 2024)
This mentoring program aims to provide comprehensive insights as a preventive effort against bullying behavior through the Pancasila Student Profile Strengthening Project at SMP Manarul Qur’an. The approach employs lecture methods combined with project-based learning, involving direct participation in poster creation and campaigning. The program begins with an initial socialization session on the concept of bullying, its impacts, and prevention strategies, conducted during the first week of mentoring. In the second week, student empowerment activities are carried out to raise awareness through investigations involving teachers and students. Subsequently, students create anti-bullying posters to voice their concerns regarding bullying threats and conduct anti-bullying campaigns alongside teachers to raise community awareness about the dangers of bullying that must be prevented. The results indicate an increase in students’ knowledge, highlighting that bullying fundamentally contradicts Islamic values and constitutes behavior that must be avoided. The acquired knowledge contributes to shaping students into individuals who are devoted to God and possess noble character. Regarding attitudes, the mentoring program effectively shifts the mindset of both victims and perpetrators, making them realize that bullying behavior is highly detrimental. It also enhances social attitudes, including mutual respect, global diversity awareness, tolerance, and empathy. In terms of skills, the service program based on the Pancasila Student Profile (P5) concept fosters the development of critical thinking related to bullying, independence and responsibility within groups, creativity, and cooperation (gotong royong) through the process of creating and campaigning anti-bullying posters.